Phantom array and stroboscopic effects of a time-modulated moving light source during saccadic eye movement. (August 2018) - Lee, C-S; Lee, J-H; Pak, H; Park, SW; Song, D-W
This paper evaluates the detectability of the phantom array and stroboscopic effects during light source motion, eye movement and their combination, using time modulated light-emitting diode light sources. It is well known that the phantom array can be observed when time-modulated light sources are observed during saccadic eye movements. We investigated whether light source motion can cause similar effects when the subject has fixed eyes. In addition, we estimated the detectability threshold frequency for the combination of stroboscopic effect and the phantom array, which is named the stroboscopic-phantom array effect, during two eye movements in opposite directions under one directional rotating light source with variable speed. Our results indicate that one of the most important factors for the stroboscopic-phantom array effect is eye movement speed relative to the speed of the light source. Therefore, time-modulated moving light sources induce a stroboscopic effect in subjects with fixed eyes that is similar to the stroboscopic-phantom array effect observed during saccadic eye movement. Our findings are likely to be useful for predicting the stroboscopic effect and the stroboscopic-phantom array effect during the fast motion of time-modulated LED light sources, like multi-functional rear lamps, in automotive lighting applications.